Effects of evidence-based strategies to reduce the socioeconomic gradient of uptake in the English NHS Bowel Cancer Screening Programme (ASCEND): four cluster-randomised controlled trials - Wardle, Jane; von Wagner, Christian; Kralj-Hans, Ines; Halloran, Stephen P; Smith, Samuel G; McGregor, Lesley M; Vart, Gemma; Howe, Rosemary; Snowball, Julia; Handley, Graham; Logan, Richard F; Rainbow, Sandra; et al. (The Lancet (British edition), 2016)
Uptake in the national colorectal cancer screening programme in England varies by socioeconomic status. We assessed four interventions aimed at reducing this gradient, with the intention of improving the health benefits of screening. All people eligible for screening (men and women aged 60–74 years) across England were included in four cluster-randomised trials. Randomisation was based on day of invitation. Each trial compared the standard information with the standard information plus the following supplementary interventions: trial 1 (November, 2012), a supplementary leaflet summarising the gist of the key information; trial 2 (March, 2012), a supplementary narrative leaflet describing people's stories; trial 3 (June, 2013), general practice endorsement of the programme on the invitation letter; and trial 4 (July–August, 2013) an enhanced reminder letter with a banner that reiterated the screening offer. Socioeconomic status was defined by the Index of Multiple Deprivation score for each home address. The primary outcome was the socioeconomic status gradient in uptake across deprivation quintiles. This study is registered, number ISRCTN74121020. As all four trials were embedded in the screening programme, loss to follow-up was minimal (less than 0·5%). Trials 1 (n=163 525) and 2 (n=150 417) showed no effects on the socioeconomic gradient of uptake or overall uptake. Trial 3 (n=265 434) showed no effect on the socioeconomic gradient but was associated with increased overall uptake (adjusted odds ratio [OR] 1·07, 95% CI 1·04–1·10, p<0·0001). In trial 4 (n=168 480) a significant interaction was seen with socioeconomic status gradient (p=0·005), with a stronger effect in the most deprived quintile (adjusted OR 1·11, 95% CI 1·04–1·20, p=0·003) than in the least deprived (1·00, 0·94–1·06, p=0·98). Overall uptake was also increased (1·07, 1·03–1·11, p=0·001). Of four evidence-based interventions, the enhanced reminder letter reduced the socioeconomic gradient in screening uptake, but further reducing inequalities in screening uptake through written materials alone will be challenging. National Institute for Health Research.